1996
DOI: 10.3109/02841869609100720
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Radiation Sensitivity and Steroid Receptor Content Induced by Hormonal Agents and Ionizing Radiation in Breast Cancer Cells in Vitro

Abstract: Possible influences of tamoxifen and estradiol on in vitro radiation sensitivity and cellular receptor content after irradiation and/or tamoxifen treatment were studied in breast cancer cell lines; estrogen receptor (ER) and progesterone receptor (PgR) positive cell lines MCF-7 and MCF-7/TAM(R)-1 and the ER and PgR negative cell line MDA-MB-231. The tamoxifen resistant MCF-7/TAM(R)-1 cells were more resistant to ionizing radiation than the MCF-7 and MDA-MB-231 cells. Exposure to tamoxifen made the MCF-7 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 19 publications
(12 reference statements)
2
24
0
3
Order By: Relevance
“…This is supported by preclinical studies showing radiotherapy to reduce ER-expression in breast cancer cell-lines and rat mammary-tumors (22)(23)(24)(25), as well as to induce ER-negative breast cancer in premenopausal mice (26). Potential explanations could be: Activation of DNA-repair pathways influencing ER-expression (23); Disturbance of ERautoregulation involving micoRNA (27,28); Microenvironmental changes inducing an ERnegative stem-cell-enriched phenotype (29); and promoter-hypermethylation reducing estrogen binding-affinity and signaling (25,28).…”
mentioning
confidence: 50%
“…This is supported by preclinical studies showing radiotherapy to reduce ER-expression in breast cancer cell-lines and rat mammary-tumors (22)(23)(24)(25), as well as to induce ER-negative breast cancer in premenopausal mice (26). Potential explanations could be: Activation of DNA-repair pathways influencing ER-expression (23); Disturbance of ERautoregulation involving micoRNA (27,28); Microenvironmental changes inducing an ERnegative stem-cell-enriched phenotype (29); and promoter-hypermethylation reducing estrogen binding-affinity and signaling (25,28).…”
mentioning
confidence: 50%
“…For establishment of long-term tamoxifen treatment, MCF-7 cells were exposed to low doses (0.01 -1 mM) of tamoxifen (Wako, Osaka, Japan) for 4 months, as detailed previously (Paulsen et al, 1996;Madsen et al, 1997). Anti-p53, anti-JNK1, anti-p38, anti-p21, antiBcl-2 and anti-actin antibodies were purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA) and a specific inhibitor of JNK (SP600125) from Calbiochem (San Diego, CA, USA).…”
mentioning
confidence: 99%
“…Although minor changes in the PGR status induced by radiotherapy should not be excluded, authors demonstrated that these receptors persisted in recurrent meningiomas and even significantly increased (P!0.02; Rubinstein et al 1994). In MCF7 breast cancer cell lines, Paulsen et al (1996) demonstrated that a radiation dose of 6 Gy reduced the ER content in cytosol, but brought no alterations to the PGR content. These results support hormone treatment for non-resectable meningiomas, especially at recurrence.…”
Section: Chargari Et Al: Endocrine Therapy In Meningioma Managementmentioning
confidence: 99%